2011
DOI: 10.4028/www.scientific.net/amr.383-390.3593
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Water Quality Remote Retrieva Based on Support Vector Regression with Parameters Optimized by Genetic Algorithm

Abstract: In order to improve water quality retrievals of multi-spectral image accurately, this paper puts forward a method for water quality remote retrieva based on support vector regression with parameters optimized by genetic algorithm. The method uses SPOT-5A data and the water quality field data, chose four representative water quality parameters, support vector regression are trained and tested, the parameters of support vector regression are optimized by genetic algorithms. The result of experiment shows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Zhang et al [58] applied PSO and genetic algorithm (GA) to optimize the parameters of SVM, and they found that PSO showed a better learning ability and generalization in wood drying process modeling. A study presented by He et al [59] indicated that PSO-SVM model is more accurate than the routine linear regression model for the water quality retrievals of Weihe River in Shanxi province. Their results demonstrated the improvement of SVM models through the optimization of PSO.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [58] applied PSO and genetic algorithm (GA) to optimize the parameters of SVM, and they found that PSO showed a better learning ability and generalization in wood drying process modeling. A study presented by He et al [59] indicated that PSO-SVM model is more accurate than the routine linear regression model for the water quality retrievals of Weihe River in Shanxi province. Their results demonstrated the improvement of SVM models through the optimization of PSO.…”
Section: Discussionmentioning
confidence: 99%
“…The current retrieval models of nitrogen and phosphorus concentrations are mainly constructed directly from remotesensing images or through media water-quality parameters such as chlorophyll a and suspended solids, and their applicability has been proved, but their models are only applicable to single water bodies (He and Li, 2011;Huang et al, 2021;Isenstein and Park, 2014;Qun'ou et al, 2021;Wang et al, 2018). It is clear that narrowing the application region of the model when constructing the retrieval model for the total phosphorus concentration in Chaohu Lake can significantly improve the retrieval accuracy (Gao et al, 2015).…”
Section: Effect Of Geographical Division On the Retrieval Accuracymentioning
confidence: 99%
“…Water quality remote sensing inversion algorithm can be roughly divided into empirical algorithm and model-based algorithm. The empirical algorithm mostly adopts a ratio method, such as hyperbolic exponential algorithm [27], binary quadratic polynomial algorithm [28], SeaWiFS algorithm [29] as well as the semi-empirical Carder model [30]. However, with the development of the bio-optical model, the quantitative inversion algorithm based on model has become the mainstream of retrieving the correlation between the water body components and the spectral radiation characteristics of water body.…”
Section: Introductionmentioning
confidence: 99%